Increased amisulpride serum concentration in a patient treated with concomitant pregabalin and trazodone: a case report - Petr Potměšil; Lenka Kostýlková; Miloslav Kopeček (SAGE Publishing, 2022)
We report on the case of a 46-year-old woman with generalized anxiety disorder, paranoid personality disorder, and mild reduction in glomerular filtration rate (GFR). She was treated with pregabalin, trazodone, hydroxyzine, and clonazepam before hospital admission. Pharmacotherapy for the patient was changed during her first week in the hospital. Dosing of hydroxyzine and clonazepam was gradually decreased, and then these two drugs were withdrawn. Treatment with amisulpride was started on the fourth day after admission, and amisulpride serum levels were then measured three times as a part of therapeutic drug monitoring (TDM). The serum concentration of amisulpride detected during concurrent use of trazodone and pregabalin was approximately twice the therapeutic range for amisulpride. When the dose of pregabalin was reduced by half, the serum concentration of amisulpride decreased to therapeutic serum levels. We hypothesize that an interaction between amisulpride and pregabalin was responsible for the increased amisulpride concentration since both drugs are almost exclusively excreted from the body by the renal route. Pregabalin-amisulpride interaction might also be influenced by concomitant therapy with trazodone or a mild reduction in GFR. However, we only have clinical evidence for an interaction between amisulpride and pregabalin because after we halved the dose of pregabalin, the amisulpride concentration decreased, and the C/D ratio normalized. This could be helpful information for psychiatrists in order to avoid drug-drug interactions between amisulpride and pregabalin. We recommend TDM of amisulpride in patients treated concomitantly with other drugs eliminated mainly by the kidneys.